TAHAPAN DAN PERSEPSI PETANI TERHADAP TRADISI NGAMBENG PARI DI DESA KEJENE - Bambang Yoga Pranoto; Harjito (STKIP Subang, 2025)
This study examines the methik and ngambeng pari traditions as part of the local wisdom upheld by the farming community of Dukuh Beber, Desa Kejene, which remain preserved within the rice cultivation cycle. These traditions are rooted in strong agrarian cultural values and are performed through meaningful ritual stages. The purpose of this research is to describe the procedural stages of the traditions and to understand farmers’ perceptions of the moral, social, and religious values embedded in them. The study employs a descriptive qualitative approach using observation, semi-structured interviews, and documentation, analyzed through the Miles and Huberman model. The findings show that the methik tradition is performed in the rice field using symbolic offerings called cokbakal, while the ngambeng tradition involves a communal feast held at home after the harvest arrives. Interviews reveal that farmers regard the traditions as expressions of gratitude and ancestral heritage that must be preserved even though they do not technically affect crop yields. The discussion links these findings with previous studies that demonstrate similar harvest rituals across Indonesia. The study concludes that these traditions hold significant spiritual and social functions for the community and remain relevant as part of the cultural identity that deserves preservation.